Challenging bias in forensic psychological assessment and testing: theoretical and practical approaches to working with diverse populations - Liell, Glenda C. (Issues in forensic psychology, 2023)
Part 1: Present day issues in forensic psychological assessment -- Introduction: Forensic Context Assessment -- Reliability, Validity, & Current Challenges / Glenda Liell, Martin Fisher and Lawrence Jones with Lorraine Hough -- Challenging Bias in the Forensic Context: Lived Experiences / Palwinder Athwal-Kooner, Martine Ratcliffe & Ana Da Silva -- The Role of Dynamic Risk Factors in Forensic Assessment and Treatment planning / Roxanne Hefferman and Tony Ward -- Why dynamic risk factors cannot be applied universally: Their normative nature and the importance of cultural awareness in risk assessment and intervention / Stefanie Schmidt, Roxanne Heffernan & Tony Ward -- The Validity of Reconviction as a Proxy Measure for Re-offending: Interpreting Risk Measures and Research in the Light of False Convictions and Detection and Conviction Evasion Skills (DACES) and processes / Lawrence Jones, Martin Fisher and Glenda Liell -- Measuring what matters: Standardized risk levels for criminal recidivism risk / Daryl Kroner and R. Karl Hanson -- The Cumulative Modelling of Risk / Sean Hamilton & Mags O'Rourke -- What Works in the Digital Age? VR and Smartphone Applications for Forensic Psychology / Aniek M. Siezenga, Jean-Louis van Gelder & Job van der Schalk -- Assessment and Intervention Technologies in Juvenile Justice / Christopher M. King, Lauren Grove, Rachel Bomysoad, Kenny Gonzalez & Loumarie Vasquez. -- Implications and Considerations for Conducting Remote Forensic Evaluations in Underserved and Marginalized Communities / Ashley Batastini, Natalie Anumba, Michelle Guyon & Meera Patel -- Part 2: Forensic practice & working with biases -- Supervising Assessment Practice / Jason Davies -- The Power Threat Meaning Framework -- Implications for the Criminal Justice System / Jo Ramsden & Kerry Beckley -- Individual Bias in Forensic Practice / Todd Hogue & Mats Dernevik. -- Cultural bias in Forensic Assessment: Considerations and Suggestions / Andrew Day, Yilma Woldgabreal & Luke Butcher -- Personal Construct Psychology & Repertory Grids in Formulation / Nicholas Blagden & Adrian Needs. -- Using Social Media Data in Forensic Evaluations: Addressing Bias / Ashley Batastini, Madison Lord & Michael Vitacco. -- Part 3: Diversity & forensic populations theoretical and practical approaches -- Gender-sensitive violence risk assessment / Vivienne de Vogel -- Critical Reflection on Gender Identity Assessments with Trans and Gender Non-Binary individuals: Challenges, implications, and a newly proposed approach in Forensic Psychology / Sören Henrich. -- Neurodiversity Assessment In Forensic Contexts / Nancy Doyle, Lorraine Hough, Karen Thorne & Tanya Banfield. -- Risk Assessment in Offenders with Learning Disabilities / Emma Longfellow, Mark Callender & Rachel Hicks. -- How forensic practitioners may better understand neurodevelopmental disorders within forensic practice with a specific focus on ADHD and ASD / Rachel Worthington. -- Deafness in a forensic context / Mats Dernevik, Brendan Monteiro, Lorraine Hough & Elizabeth Kimber -- Criminally Diverse Offenders / Phillip Willmot -- Challenging Bias in the Assessment of Extremist Offending / Christopher Dean & Monica Lloyd. -- The Assessment of Psychopathy / Jake Seaward & Jenny Tew. -- Technological assessment methods: New directions in the assessment of sexual offending and sexualised violence / Derek Perkins and Ignazio Puzzo -- Future direction -- Challenging bias in cross-cultural forensic psychology assessment and testing: A summary perspective / Yilma Woldgabreal.